Comparison of the protective effect of alpha lipoic acid and quercetin in methotrexate- induced lung damage - AK, ESİN; OKTAY, NİHAL ŞEHKAR (My University, 2023)
Objective: The aim of this experiment is to investigate and compare the effects of alpha lipoic acid (ALA) and quercetin (QUE) on methotrexate (MTX)-induced lung injury in rats. Method: Wistar Albino rats were distributed into control, MTX, MTX+ALA and MTX+QUE groups with each consisting of 6 rats. Except control group, MTX administrated to rats as a single dose (20 mg/kg) intraperitoneally (i.p.) on the first day. Saline (0.1 cc/100 gr/day, i.p.) was injected to rats in control and MTX groups for 5 days. In MTX+ALA and MTX+QUE groups, rats had injections of ALA (50 mg/kg/day, i.p.) and QUE (50 mg/kg/day, i.p.) for 5 days. After sacrification on day 6, lung tissues were excised out for histopathologic and biochemical investigation. Results: MTX group showed massive hemorrhage with edema in the interstitium, significant inflammatory cell infiltration, and severe alveolar destruction and vascular congestion. Additionally, significant increases in oxidative stress markers as malondialdehyde and sialic acid and significant decreases in antioxidants as glutathione, superoxide dismutase and catalase were detected at the tissue level in MTX group (p<0.0001, p<0.0001, p<0.0001, p=0.03 and p<0.0001, respectively). Both ALA and QUE treatment led to a prominent improvement in morphologic damage. Moreover, ALA and QUE resulted in the reversal of the alterations seen in the tissue oxidative damage markers and antioxidant activities as well. We could not reveal a significant difference between MTX+ALA and MTX+QUE group in terms of morphologic damage and biochemical markers of oxidative injury (p>0.05). Conclusion: Our study showed the similar protective effect of ALA and QUE in MTX induced lung damage. Further studies are warranted to verify the results of our outcome.

Amaç: Bu çalışmanın amacı sıçanlarda metotreksat (MTX) ile oluşturulan akciğer hasarında alfa lipoik asit (ALA) ve kuersetinin (QUE) koruyucu etkilerinin araştırılması ve karşılaştırılmasıdır. Yöntem: Wistar Albino her biri 6 adet sıçandan oluşan kontrol, MTX, MTX+ALA ve MTX+QUE gruplarına ayrıldı. Kontrol grubu hariç tüm gruplarda deneyin ilk gününde sıçanlara tek doz MTX (20 mg/kg) intraperitoneal (i.p.) olarak verildi. Kontrol ve MTX gruplarındaki sıçanlara 5 gün serum fizyolojik (0,1 cc/100 gr/gün, i.p.) verildi. MTX+ALA ve MTX+QUE gruplarındaki sıçanlara 5 gün ALA (50 mg/kg/gün, i.p.) ve QUE (50 mg/kg/gün, i.p.) enjeksiyonu yapıldı. Deneyin 6. gününde sıçanlar sakrifiye edilerek akciğer dokuları histopatolojik ve biyokimyasal inceleme için çıkartıldı. Bulgular: MTX grubunda interstisyumda yoğun hemorajiyle birlikte ödem, belirgin enflamatuvar hücre infiltrasyonu ve ciddi alveolar yıkımı ve vasküler konjesyon görüldü. Bu bulgulara ek olarak, MTX grubunda malondialdehit ve sialik asit gibi oksidatif stres belirteçlerinde önemli bir artış ve glutatyon, süperoksit dismutaz ve katalaz gibi antioksidanlarda önemli bir azalış olduğu doku düzeyinde saptandı (sırasıyla p<0,0001, p<0,0001, p<0,0001, p=0,03 ve p<0,0001). Hem ALA hem de QUE tedavisinin morfolojik hasar üzerinde belirgin bir iyileşmeye neden olduğu tespit edildi. Ayrıca ALA ve QUE tedavisi MTX’in yol açtığı doku oksidatif hasar belirteçlerinde ve antioksidan aktivitedeki olumsuz değişimleri tersine çevrilmesine neden olduğu tespit edildi. Morfolojik hasar ve oksidatif hasarın biyokimyasal belirteçleri açısından MTX+ALA ve MTX+QUE grupları arasında anlamlı bir fark saptanmadı (p>0,05).Sonuç: Çalışmamız MTX ile oluşturulan akciğer hasarı üzerinde ALA ve QUE’nin benzer koruyucu etkilerinin olduğunu gösterdi. Sonuçlarımızı doğrulamak için daha ileri çalışmalara ihtiyaç duyulmaktadır.
Keywords: Alpha lipoic acid; lung; methotrexate; quercetin; Akciğer; alfa lipoik asit; kuersetin; metotreksat